2002
DOI: 10.1017/s0142716402003041
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the integration of information from context and word parts in interpreting unknown kanji words

Abstract: This study examines individual differences in the ability to integrate information from word parts and context in interpreting novel kanji compounds (i.e., words consisting of two or more Chinese characters). To account for different approaches that students take to infer the meanings of unfamiliar words, the study also investigates the relationship between students' beliefs about the effectiveness of using kanji and/or contextual clues and their abilities to use the clue(s). A total of 74 English-speaking col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 27 publications
0
39
0
2
Order By: Relevance
“…In other words, the students knew the individual kanji characters used in the target kanji words, but not the target words. 2 Mori (2002a) further investigated the inability to integrate internal and external information and suggested that the inability to integrate information from two sources was correlated with the students' belief in the efficacy of an integration strategy. 3 With the phonographic writing system, the basic unit of representation is a phoneme, a sound unit (e.g., kana in Japanese, English alphabet), whereas with the morphographic writing system, the basic unit is a morpheme that represents a meaning (e.g., Chinese characters).…”
Section: Revised Version Accepted 5 August 2005mentioning
confidence: 99%
“…In other words, the students knew the individual kanji characters used in the target kanji words, but not the target words. 2 Mori (2002a) further investigated the inability to integrate internal and external information and suggested that the inability to integrate information from two sources was correlated with the students' belief in the efficacy of an integration strategy. 3 With the phonographic writing system, the basic unit of representation is a phoneme, a sound unit (e.g., kana in Japanese, English alphabet), whereas with the morphographic writing system, the basic unit is a morpheme that represents a meaning (e.g., Chinese characters).…”
Section: Revised Version Accepted 5 August 2005mentioning
confidence: 99%
“…However, a series of studies by Mori (1999;2002;Mori & Nagy, 1999) produced different results from those of Pike (1979) and Henning (1991). She used Japanese vocabulary tests and compared three conditions: kanji only, context only, and kanji and context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2003a). At the same time, students show considerable individual differences in the way they learn new kanji words (Kubota & Toyoda 2001;Y. Mori 2002).…”
Section: Vocabulary and Kanji Learningmentioning
confidence: 99%